(untitled) (JURNAL TABGHA, 2022)
The purpose of this research is to describe the impact of leadership with Christian integrity and work motivation as employees on the quality of service to customers at Permata Bank Batam. The scope of this research are motivation and leadership variable where in an organization the impact of a leader greatly affects the work that is the target of the achievement of the business process. This research method uses library analysis to explore some of the lives of Christian integrity characters and a quantitative approach using multiple regression analysis to measure the influence between variables partially and the Anova test to measure the percentage of impact strength between variables, while the data analysis instrument uses SPSS. The results of this study from the R coefficient that the independent variables of Christian integration and work motivation contribute to the improvement of service quality to customers at Permata Bank Batam by 43.1%. The role of leadership with Christian integrity and motivation is proven to be able to improve staff services to customers at Permata Bank. A successful leader must have real Integrity in every leadership he carries out. Leaders with Christian integrity have proven to be needed and able to motivate the running of qualified operational activities and improve services to customers at Bank Permata Batam.